Concrete cracking in new bridge decks and overlays - Foley, Christopher; Wan, Baolin; Komp, Jordan (Wisconsin Highway Research Program, 2010)
There appears to be a trend for new bridge decks in the state of Wisconsin to develop early-age transverse cracks and map cracks on concrete overlays. A comprehensive literature review of the potential causes of concrete bridge deck cracking is provided. Fifteen bridge structures found in the recently completed Marquette Interchange were analyzed using 21 variables thought to cause early-age bridge deck cracking. Visual inspection of sixteen bridges in Milwaukee is described. The inspections show that the continuous superstructures have more cracks than the simply-supported bridges. A finite element model was created for a typical two-span continuous superstructure with HL-93 truck loads and concrete shrinkage-induced strains. The FE simulations indicate that the normal traffic load by itself will not cause concrete deck cracking. However, tensile stress introduced by concrete shrinkage may cause transverse cracks as early as 4 to 8 days after pouring concrete. Concrete samples were taken from two continuous superstructure bridge decks and unconfined compression testing was conducted. The experimental results indicate that the decks? 28-day unconfined compression strength of the concrete was much higher than the design target. Furthermore, the unconfined compression strength at 3-5 days is very near the target 28-day unconfined compression strength. The rapid development of compression strength and elastic modulus may result in significant shrinkage and tensile stresses in the deck, and therefore early age cracking in bridge decks. Recommendations for reducing deck cracking and future research are provided.
154 p.
Keywords: Cracking; Bridge decks; Overlays (Pavements); Concrete; Finite element method